Optimalisasi Prestasi Belajar Materi Pembelaan Negara Melalui Pendekatan Mastery Learning di SMP - Priyanta, Priyanta (Manajemen Pendidikan, 2015)
This  research  surrounded  by  still  have  not  optimal  of domination  of matter Country  of  Protection  among  student  and  implementation   of  approach  of  mastery learning. This research aim to description  about optimalisation  of domination  of matter Country   protection   through   approach   of  mastery   learning   in  study  of  Education Citizenship  at class student IX C State Junior High School Two Cawas Region Klaten even semester of school year 2013/2014. Subject and research data source is 20 students. Data  collecting  method  applies  observation,  documentation,   and  test.  Data  analysis applies  critical  analysis  and  comparability.  Indicator  success  of  using  KKM  75  and complete target of class 100%. Research procedure applies cycle. Result of research and solution  it  is  by  know  that  data  obtained  from  finite  precycle  of  cycle  II,  obtained progress  of  achievement  of  student  learning  in  study  of  Education  Citizenship  with matter Country of Protection through approach of mastery learning, at precycle average of 72,1 and cycle I average of 73,9 and cycle II average of 86,2. From this data, seems to explain that happened increase of average of value from precycle to cycle I 1,8 numbers (2,5%), from cycle I to cycle II happened increase 12,3 numbers (16,6%), from pasiklus to cycle II happened increase 14,1 numbers (19,6%). Highest value of phase precycle 80 and cycle  I 82 and cycle  II 96. Seems  to explain  that  from  phase  precycle  to cycle  I happened increase equal to 2 number (2,5%), from cycle I to cycle II happened increase14  numbers  (17,1%),  and  from  precycle  to  cycle  II  happened  increase  16  numbers (20%).  Low value of phase precycle  is obtained  by 64 and cycle I 68 and cycle II 78. thereby, can be affirmed that from phase precycle to cycle I happened increase equal to 4 number  (6,3%),  from  cycle  I to cycle  II happened  increase  10 numbers  (14,7%),  and from precycle  to cycle II happened  increase 14 numbers  (21,9%).  Complete  percentage learnt starts from precycle is obtained equal to 20% and cycle I is obtained equal to 30% and  cycle  II  equal  to  100%.  Seems  to  explain  that  from  phase  precycle  to  cycle  I happened increase equal to 10%, from cycle I to cycle II happened increase equal to 70%, and from precycle to cycle II happened  increase equal to 80%. Thereby, achievement  of student learning in study of Education  Citizenship  with matter Country of Protection through approach of mastery learning from finite precycle of cycle II happened increase significant.